Genetic Diversity Between and Within Astrocaryum acaule Mart. (Arecaceae) Populations - Aline Araújo Patrício Lima; Maria Teresa Gomes Lopes; Mágno Sávio Ferreira Valente; Santiago Linorio Ferreyra Ramos; Edvan Alves Chagas; Júlio César Gonçalves de Souza (Floresta e Ambiente, 2020)
Abstract This article sought to assess the genetic diversity within and between natural populations of Astrocaryum acaule by means of AFLP markers. Ninety individuals were sampled in three populations located in Manaus (state of Amazonas) across regions with different intensities of anthropogenic activity. Two clusters were differentiated by means of dendrograms and Bayesian cluster analysis, the first consisting of individuals from the Tarumã-Açu population in an intensely agricultural region, and the second, of populations from UFAM and Tupé conservation areas. The physical isolation of A. acaule populations has resulted in good conservation of its genetic identity, since anthropogenic activity is an important modifier of the genetic diversity of natural populations. Genetic diversity was higher within populations (74.58%) than between them (25.42%), which means that we have to collect representative samples from each of the genetically distinct groups for genetic conservation of the species. Therefore, in situ conservation is recommended.